2021
DOI: 10.1080/1750399x.2020.1856023
|View full text |Cite
|
Sign up to set email alerts
|

Information behaviour in bidirectional translators: focus on online resources

Abstract: Effective information behaviour is crucial in all translation competence models but our understanding of how information skills develop and how translators interact with information found in online resources is still limited. In this article we focus on information behaviour (needs and use) of bidirectional translators who frequently translate into their native (L1) and their non-native language (L2). The theoretical underpinnings come from information studies: (1) information is needed when cognitive uncertai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
0
10
0
1
Order By: Relevance
“…66 When faced with ambiguities or difficulties during translation, translators can find feasible and quick solutions with the help of electronic dictionaries, online knowledge-sharing platforms, and search engines. 67,68 The introduction of the internet has also dramatically expanded the information sources accessible to translators, transformed the way of searching for information in translation activities, and improved the effectiveness and efficiency of the information-seeking process. 69,70…”
Section: Dovepressmentioning
confidence: 99%
“…66 When faced with ambiguities or difficulties during translation, translators can find feasible and quick solutions with the help of electronic dictionaries, online knowledge-sharing platforms, and search engines. 67,68 The introduction of the internet has also dramatically expanded the information sources accessible to translators, transformed the way of searching for information in translation activities, and improved the effectiveness and efficiency of the information-seeking process. 69,70…”
Section: Dovepressmentioning
confidence: 99%
“…The Internet has changed the way translators consult information, shifting from traditional resources such as printed dictionaries to digital forms. With the Internet and smart devices, translators can get easy access to a huge range of online resources that help them to gain useful information effectively and efficiently (Daems et al, 2016;Whyatt et al, 2021).…”
Section: Literature Review and Hypothesis Development Online Informat...mentioning
confidence: 99%
“…In translation studies, online information seeking has been found to be significantly correlated with translation process (e.g., Hvelplund, 2019;Sycz-Opoń, 2019;Prieto Ramos, 2020). Previous studies have shown that online resources such as search engines, electronic dictionaries, and specific portals, as compared with seeking information from print resources, enable translators to acquire better information in a more efficient way when they experience uncertainty in the problem-solving process (e.g., Hvelplund, 2017;Kuznik and Olalla-soler, 2018;Whyatt et al, 2021). However, mixed findings were reported on the impact of online information seeking on translation performance.…”
Section: Introductionmentioning
confidence: 99%
“…The use of resources in the translation and interpreting process is related to information behaviour, which is defined as all behaviours related to information people receive and exchange, including media use and all the communication activities between people (Jiang, 2019). Previous studies related to information behaviour examine the search strategy used in the translation process (Whyatt, Witczak, & Tomczak, 2021), the behaviours of students and professional translators in web searching (Ohnishi & Yamada, 2020), the interaction between translator and computer (Bundgaard, 2017), and between translator/interpreter and information (Havnen, 2021). It may be concluded that research on this particular topic has become more pragmatic, focusing on problem-solving for technology development, time efficiency, and high quality to meet the global market demand.…”
Section: Introductionmentioning
confidence: 99%